Collaborative Governance dalam Peningkatan Mutu Pendidikan di Era Digital: Comparative Literature Review Pada Kota Yogyakarta, Surabaya, dan Sulawesi Selatan - Prasetiyono, Bagus; Musleh, Moh.; Yuwono, Rudy; Maharani, Nabila (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study aims to analyse the application of collaborative governance in improving the quality of education in the digital age through a comparative literature review of the cities of Yogyakarta, Surabaya and South Sulawesi. The method employed is a systematic literature review using a qualitative-descriptive approach and cross-case synthesis, drawing on the collaborative governance framework by Ansell and Gash, which encompasses starting conditions, institutional design, facilitative leadership, and collaborative process. The article search process was conducted via scientific databases such as Google Scholar, Scopus, and SINTA using the keywords “collaborative governance”, “digital education”, and “quality of education”. Inclusion criteria included articles relevant to the educational context, published between 2015 and 2025, and focusing on multi-stakeholder collaboration in educational governance. Based on a systematic selection process, approximately 30 articles were identified for in-depth analysis. The findings indicate that the success of collaborative governance in improving educational quality is significantly influenced by initial conditions such as educational and digital divides, adaptive institutional design, contextual facilitative leadership, and participatory and sustainable collaborative processes. Comparatively, the City of Yogyakarta tends to develop community- and digital-based collaboration models, Surabaya stands out in its institution-based approach and school practices, whilst South Sulawesi demonstrates a more structured collaboration model based on bureaucratic systems. These findings confirm that collaborative governance in education in the digital age is contextual and multidimensional, thus requiring an adaptive approach tailored to regional characteristics.